Wokół pierwszej polskiej systematyki zamówień. O zapomnianej propozycji Józefa Obrębskiego - Engelking, Anna (Wydawnictwo Naukowe UAM, 2012)
The author discusses the first Polish systematics of magic spells against illness, which was proposed by Józef Obrębski in a brochure Index for „Treating the Polish people” by Henryk Biegeleisen in 1931. Obrębski introduced a division of spells into 9 groups, separated on the basis of their content, form and function. It was not an autonomous development. It have been created for the needs of someone else’s work and on the margin of a broader classification of material in the field of folk medicine as a whole. However, the proposal of Obrębski can be regarded as a serious outline covering all material concerning the systematics of spells against illness. In the following parts of the article the author sets the discussed work in a due context, locating it in the history of Polish research on the genre of spells. She recalls the first nineteenth-century works and analyses a possible impact of the Obrębski’s systematics on the subsequent approaches to the subject.
The First Polish Systematics of Spells against Illness. On the Forgotten Proposal of Józef Obrębski
Keywords: spells; folk medicine; systematics; literary genetics; the history of folklore; the history of ethnology